2012
DOI: 10.4103/2045-080x.106255
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of fourth year Doctor of Pharmacy students towards pharmacy profession and their career preferences

Abstract: Objectives:To identify fourth year Doctor of Pharmacy (Pharm.D) students' attitude towards pharmacy profession, their career preferences, and factors involved in this selection. Materials and Methods: A pre-designed questionnaire was administered to fourth year Doctor of Pharmacy (Pharm.D) students. Information were collected regarding students' attitude about the scope of pharmacy, career preferences, and factors influencing their selection, impact of pharmacy profession on health care system, and post-gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Work environment and advancement were also reported as significant contributors in many studies [ 12 , 13 ]. However, the order of the importance of factors were not similar in different studies; while the most important factors reported in a Saudi study [ 8 ] were salary, job promotions and job opening, personal interest was reported as the most important factor by a Pakistani study [ 14 ]. PharmD students had a significantly higher mean in considering work experience as an important factor in their career choice compared to pharmacy students; this difference was not found in the previously mentioned Saudi study [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Work environment and advancement were also reported as significant contributors in many studies [ 12 , 13 ]. However, the order of the importance of factors were not similar in different studies; while the most important factors reported in a Saudi study [ 8 ] were salary, job promotions and job opening, personal interest was reported as the most important factor by a Pakistani study [ 14 ]. PharmD students had a significantly higher mean in considering work experience as an important factor in their career choice compared to pharmacy students; this difference was not found in the previously mentioned Saudi study [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of our research are related to different investigations that decided lacking information and awareness of college scholars toward biotechnology before they get admission [26][27][28][29][30]. A vast majority of studies were pointing to mindfulness and information toward biotechnology among the overall population.…”
Section: Discussionmentioning
confidence: 95%